Mobilni multimedijski terminal v transfuzijski praksi - Meža, Marko (Zdravniški vestnik, 2004)
Background. Due to the administrative errors in the transfusion chain between the blood donor and the patient, transfusion errors still occur. Usually, theyare caused by the misidentifications of the patient, his blood samples andrespective blood components. A reliable identification can only be reached by an appropriate informatization of the whole process by implementation of information networks and communication technologies. Methods. An information system covering all modern standards of safety and enabling integrity of patient records as well as faster and efficient transfusion was prepared. The system is enabling the rational use of the blood as well as assuring the obligatory haemoviligilance, as foreseen by the current law. The whole system is modular, consisting of terminals, supportive equipment, networking systems and servers. Additional hardware are the electronic code bar readers. Mobile terminals (Palm Pocket PCs) are wirelessly connected to the data network usingthe IEEE 802.11 b WLAN technology in a wireless connection. All elements are included into the communication network with the servers contain data bases of blood donors, blood components and the patients; they execute the algorithms of the blood transfusion process support and enable the authentication. At the same time they enable the corresponding interfaces adapted to the users and terminals. For the connection of elements, corresponding interfaces are used. Results. The application is supporting the whole system of ordering, issuing and transfusion of a blood component Its main characteristics are the bar-coded wristband for patient identification, coding of the blood samples with the same bar code that is unmistakably connected with the patient, and electronic ordering of blood component via a handheld device at the patient's side. (Abstract truncated at 2000 characters).
Keywords: Blood Transfusion; Bolnik, identifikacijski sistemi; Health Services; Krvna transfuzija; Medical Records; Medicinske kartoteke; Organization And Administration; Patient Identification Systems; Zdravstvene službe